Cranioplasty for Large-Sized Calvarial Defects in the Pediatric Population: A Review. Issue 2 (June 2015) - Lam, Sandi; Kuether, Justin; Fong, Abigail; Reid, Russell
Large-sized calvarial defects in pediatric patients pose a reconstructive challenge because of children's unique physiology, developing anatomy, and dynamic growth. We review the current literature and outcomes with autologous and alloplastic cranioplasty in the pediatric population.